1997
DOI: 10.1111/j.1469-7793.1997.135bf.x
|View full text |Cite
|
Sign up to set email alerts
|

Membrane currents underlying the modified electrical activity of guinea‐pig ventricular myocytes exposed to hyperosmotic solution

Abstract: Guinea‐pig ventricular myocytes were superfused with hyperosmotic (sucrose) Tyrode solution (1.2–2.8 times (T) normal osmolality) for up to 40 min. Action potentials were recorded with microelectrodes, and membrane currents with the perforated‐ or ruptured‐patch technique. Hyperosmotic treatment for 20 min shrunk cell volume and hyperpolarized the membrane. Moderate (1.2–1.5T) treatment caused biphasic changes in action potential configuration (rapid minor shortening quickly followed by lengthening to a stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 35 publications
3
34
1
Order By: Relevance
“…Guinea pigs (250-350 g) were anesthetized with sodium pentobarbital (50 mg · kg Ϫ1 , I.P.). Hearts were quickly excised, and single ventricular myocytes were enzymatically isolated as described previously [10]. In brief, the excised hearts were mounted on a Langendorff column and perfused (37°C) with Ca 2ϩ -free Tyrode's solution containing collagenase (ϳ0.1 mg · ml…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guinea pigs (250-350 g) were anesthetized with sodium pentobarbital (50 mg · kg Ϫ1 , I.P.). Hearts were quickly excised, and single ventricular myocytes were enzymatically isolated as described previously [10]. In brief, the excised hearts were mounted on a Langendorff column and perfused (37°C) with Ca 2ϩ -free Tyrode's solution containing collagenase (ϳ0.1 mg · ml…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with 0.1 mM Hg 2ϩ , a sulfhydryl-oxidizing reagent, reduced P f by ϳ90%, and the sulfhydryl-reducing reagent dithiothreitol (10 ) was in the range of that for diffusional water movement through the lipid bilayers (Ͼ10 kcal · mol cient (P f ) was obtained from the time course of cell swelling and shrinkage in response to rapidly imposed osmotic gradients. The results demonstrate that the myocytes exhibit osmometer-like behavior with an apparent osmotically dead space of nearly one-third of their volume.…”
mentioning
confidence: 99%
“…Furthermore, it has been shown that the increased blood tonicity in streptozotocin-induced diabetic rats leads to shrinkage of ventricular myocytes [5] . Many previous studies have indicated that both electrical and contractile properties of ventricular myocytes are affected by osmotic stress [1,[5][6][7][8][9] . For example, it has been consistently found that L-type Ca 2+ currents, Ca 2+ transients and contraction evoked by action potential are decreased by prolonged exposure to hyposmotic medium [1,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Increase in extracellular osmolality causes rapid loss of cell water, leading to a decrease in cell volume and an increase in the intracellular concentration of several solutes, including Na + [1,14,30,50]. In cardiac myocytes, cell shrinkage is not instantaneous but develops over 1-2 min and is not followed by regulatory volume increase up to 20 min of sustained hyperosmolality in the case of solutes with a high reflection coefficient, such as sucrose ( [35,38,50]; present results). Shrinkage of junctional SR, described in skeletal muscle fibers exposed to hyperosmotic sucrose solutions [17,33], might increase intra-SR [Ca 2+ ], even if the amount of Ca 2+ stored in the organelle is unaffected.…”
Section: Effects On [Ca 2+ ] Imentioning
confidence: 46%
“…We estimate that after 1 min exposure to the HNaCl solution, [Na + ] i would be ∼15% higher because of cell shrinkage. Still, the driving force for NCX-mediated Ca 2+ efflux would be at least 16 mV greater than under baseline conditions (or even more, if we consider the ∼5-mV contribution of the diastolic hyperpolarization caused by hyperosmolality [14,26,30,38,46]). Greater Ca 2+ extrusion by NCX does not only decrease cell Ca 2+ load but also gradually increases [Na + ] i , and both changes contribute to revert the initial positive shift in the exchanger reversal potential, thus limiting SR Ca 2+ unloading and depression of systolic Ca 2+ transients.…”
Section: Effects On [Ca 2+ ] Imentioning
confidence: 97%